Imagining Utopia figuring an Asian neighbourhood - Ramirez, Eileen Legaspi (Philippine Humanities Review:Rebyu ng Arte at Literatura ng Pilipinas, 2013)
The essay attempts to identify aspects of problems that continue to confront art managers and curators who practice exhibition-making in contested territories perceived as critically determining a political construction such as Asia, a site and space for representation. The proposed exhibition, which initially propelled this research, was called United States of Asia (USAsia or US of Asia) and was primarily intended as a parody of a foolhardy mythic imaging of shared agendas whereas skewed power dynamics continue to prevail. Amongs the most prominent problems plaguing the proposal development phase of US of Asia was the dearth of resources lent to the key task of on-the-ground research as opposed to the mere assemblage of 'international spectacle' or superficially celebratory parading of national colours.